2020
DOI: 10.3390/plants9101389
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Nutrient Management through Synchronization of Application Methods and Rates in Wheat and Maize Crops

Abstract: Management of inorganic fertilizer is very important to obtain maximum crop yield and improved nutrient use efficiency in cereal crops. Fixation of phosphatic fertilizers in alkaline soils due to calcareousness is one of the major hurdles. It induces phosphorus nutritional stress that can decrease the yield of maize and wheat. Selection of a suitable application method and proper stage of crop for phosphorus (P) fertilizer has prime importance in better uptake of P and crop production. Among different applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Application of NPK (150:125:250) and microbial consortia (MC) comprising nitrogen fixers, P and Zn solubilizing PGPR, and Arka Actino plus (AAP) containing Streptomyces sp., as a biopesticide is known to improve the soil enzyme activities [56][57][58][59]. Use of Biostimulants and foliar application of fertilizer reduces the need for fertilizer [60][61][62][63][64][65][66][67]. However, the literature showed no studies on the analyses in soil enzyme activities, soil agrochemical, and chemical properties in cultivated turmeric in Uzbekistan.…”
Section: Discussionmentioning
confidence: 99%
“…Application of NPK (150:125:250) and microbial consortia (MC) comprising nitrogen fixers, P and Zn solubilizing PGPR, and Arka Actino plus (AAP) containing Streptomyces sp., as a biopesticide is known to improve the soil enzyme activities [56][57][58][59]. Use of Biostimulants and foliar application of fertilizer reduces the need for fertilizer [60][61][62][63][64][65][66][67]. However, the literature showed no studies on the analyses in soil enzyme activities, soil agrochemical, and chemical properties in cultivated turmeric in Uzbekistan.…”
Section: Discussionmentioning
confidence: 99%
“…Alzreejawi and Al-Juthery [114] recorded the significant superiority of Nano-NPK (12-12-36) spray in achieving the highest means values for chlorophyll content in leaves, plant height, stem diameter, biological yield, grain yield, and harvest index. Rafiullah et al [115] reported that fixation of phosphate fertilizers in alkaline calcareous soil was a major obstacle that could decrease the yield of maize and wheat. Foliar P on maize significantly enhanced grain yield and phosphorus use efficiency.…”
Section: Effects Of Npk Fertilizermentioning
confidence: 99%
“…Scarcity of good quality water for irrigation creates the majority of lethal stress among all abiotic stresses (i.e., heavy metals, nutrients), called drought [1][2][3][4][5]. Uneven and low rainfall, dry winds, and temperature dynamics are common factors that promote the development of drought conditions [6].…”
Section: Introductionmentioning
confidence: 99%